LITURGY, MODERNITY, AND IDEOLOGY: Reflections on Similarities and Differences between Trent and Vatican II - Geldhof, Joris (Asian Horizons, 2013)
One often hears that the Roman Catholic Church only opened its windows for the modern world at Vatican II. This is a curious statement, however, for it supposes an understanding of modernity which may be questioned for good reasons. Actually, it means that the Church had missed the boat of contemporary (Western) society for a very long time. At the same time, it implied the hope that the Church would soon adopt a (more) democratic culture, that churchleaders would attach (more) importance to the idea that every baptized person is an equal member of the Church understood as the peregrinating people of God, and that corresponding proposals would be implemented to modify procedures of decision-making in the Church at large. When it comes to the liturgical life of the Church, this position usually favours the active participation of all the faithful in worship services of all kinds, celebrations of the Eucharist, the sacraments and the Liturgy of the Hours in vernacular languages, and an overall easy access to the Church’s ritual and ceremonial repertoire.